Determinants of esophageal varices bleeding in patients with advanced hepatocellular carcinoma treated with sorafenib. Issue 3 (1st June 2016) - Iavarone, Massimo; Primignani, Massimo; Vavassori, Sara; Sangiovanni, Angelo; La Mura, Vincenzo; Romeo, Raffaella; Colombo, Massimo
Abstract : Background and aims: Sorafenib is the standard of care for patients with advanced hepatocellular carcinoma (HCC), yet treatment safety may be challenged by portal hypertension. We therefore assessed the prevalence, risk factors and clinical consequences of esophageal varices (EVs) in sorafenib‐treated patients with HCC. Methods: Starting in 2008, all compensated patients with advanced or intermediate HCC not eligible for other therapies were consecutively enrolled in a prospective evaluation of sorafenib therapy, all with pretreatment by upper‐gastrointestinal endoscopy (UGE). Results: A total of 150 patients received sorafenib for 4.6 (95% CI, 3.3–5.6) months. At baseline, 61 (41%) patients were EV free (group A), 78 (52%) had EVs (61 small EVs (group B), 17 medium/large EVs (group C)) and 11 (7%) previously endoscopically treated EVs (group D). Propranolol was given to all patients with medium/large EVs and those with previous bleeding. Twelve patients (8%) bled from EVs after 36 (18–260) days of sorafenib. During sorafenib, bleeding occurred in six of 26 group B patients with neoplastic portal vein thrombosis (nPVT), three of nine group C patients with nPVT, two of five group D patients with nPVT and one of six without nPVT ( p < 0.0001), nPVT being the strongest independent predictor of bleeding by multivariate analysis (HR = 15.4, 95% CI 1.84–129.6). Conclusion: UGE screening is worthwhile in HCC patients allocated to sorafenib since it identifies patients with EVs at risk of bleeding during therapy, particularly those with nPVT.